INDONESIAN ECONOMIC THE IMPACT OF COVID 19 (IHSG BY ARDL) - Novalina, Ade; Ramli, Ramli; Daulay, Murni; Ruslan, Dede (International Proceeding of Law and Economic, 2020)
This researcher discusses the economic problems that occurred due to the first Covid-19 virus in China. The outbreak of coronavirus has caused real harm among the people of the world. Indonesia also experienced this loss in various sectors, especially the economic sectors. The COVID-19 epidemic quickly spread to all parts of the world, reaching 187 countries with 294,110 confirmed cases and 12,944 deaths and predicted to cause an economic crisis. One of the impacts seen from this C.O.V.I.D. outbreak, the decline of J.C.I. from 6299,539 in December 2019 to 4194,944 on March 20, 2020. A specific target in this study is to look at the impact of the COVID-19 epidemic on the Combined Share Price Index, Trading Sector, and Financial Sector. This research uses the A.R.D.L. model approach, the Autoregressive Distributed Lag (A.R.D.L.) method, to determine the movement of trade indices and finance indices affecting the flow of J.C.I. in the period October 1, 2019- March 20, 2020. The expected result of all analysis is to find the Leading Indicator of J.C.I. Movements, which are based on the influence of Sectoral Indices, trade, Finance during the Covid-19 Epidemic. The results of research on the evolution of the value of J.C.I., sector trade index and sector finance index in the period October 1, 2019- March 20, 2020, showed the COVID-19 pandemic would affect the economy in Indonesia. This research uses the A.R.D.L. model approach to determine the movement of trade indices and finance indices affecting the flow of J.C.I. in the period October 1, 2019- March 20, 2020, and the results obtained by finance indexes and trade indices are proven to have long-term cointegration or move together – the same long-term against J.C.I. Also, the three variables have a short-term relationship dynamic that has a speed of adjustment towards a balance of 17.21% % per day. This condition shows that the trade sector and sector trade influence the financial industry, especially the capital market. Keywords: Law, Economic, Pandemic, New Normal.